Genome Mining for Innovative Biocatalysts: New Dihydroxyacetone Aldolases for the Chemist's Toolbox. Issue 12 (15th June 2015) - Guérard‐Hélaine, Christine; de Berardinis, Véronique; Besnard‐Gonnet, Marielle; Darii, Ekaterina; Debacker, Marine; Debard, Adrien; Fernandes, Carlos; Hélaine, Virgil; Mariage, Aline; Pellouin, Virginie; Perret, Alain; Petit, Jean‐Louis; et al.
Abstract Stereoselective carboligating enzymes were discovered by a genome mining approach to extend the biocatalysis toolbox. Seven hundred enzymes were selected by sequence comparison from diverse prokaryotic species as representatives of the aldolase (FSA) family diversity. The aldol reaction tested involved dihydroxyacetone (DHA) and glyceraldehyde‐3‐phosphate. The hexose‐6‐phosphate formation was monitored by mass spectrometry. Eighteen enzymes annotated either as transaldolases or aldolases were found to exhibit a DHA aldolase activity. Remarkably, six of them proven as aldolases, and not transaldolases, shared very limited similarities with those currently described. Multiple sequence alignment performed on all enzymes revealed a Tyr in the new DHA aldolases as found in FSAcoli instead of a Phe usually found in transaldolases. Four of these DHA aldolases were biochemically characterised in comparison with FSAcoli. In particular, an aldolase from Listeria monocytogenes exhibited interesting catalytic properties.